The Motives of Selecting Majors among Students of the Faculty of Arts, Khartoum University, Sudan - Mohamed, A. Elhaj; Asmaa S. Fath Elrahmaan (University of Science and Technology, Yemen, 2020)
The study aimed to identify the general attribute of the motives for selecting majors by the students of the Faculty of Arts at Khartoum University, Sudan, and to identify the differences pertinent to a number of variables. To achieve this, the researchers used the descriptive analytical method, and developed an inventory of the motives for selecting majors. The inventory was administered to a sample of (149) individuals (39 males, 110 females), selected by the stratified random method.  For the data analysis, the researchers used T- test for a single sample, T-test for two independent samples, on-way variance analysis and Tukey test. The study revealed these results: the motives for selecting majors by students were low; and there were no statistically significant differences attributed to gender, marital status, study level, father's level of education (except for the psychological factor in favor of post-graduate education), and mother's level of education. There were statistically significant differences attributed to hometown in favor of students from urban areas. The study concluded with a number of recommendations, including the necessity of organizing orientation meetings and workshops by the Faculty Administration to make students aware of the nature of the majors in the Faculty of Arts at  Khartoum University. Keywords: motives, selection of majors, Khartoum University, Sudan.